ISOLATION AND IDENTIFICATIONOF EIMERIASCHNEIDER, 1875 SPECIES(APICOMPLEXA, EIMERIIDAE) FROM GOATS IN WASIT PROVINCE, IRAQ - Zainab A. Makawi (Bulletin of the Iraq Natural History Museum)
Eimeriosis is a major problem affecting ruminants worldwide. The disease is primarilycaused by Eimeriaspecies, whichare specialized for each host and grow in the small and large intestine of animals. The losses due to subclinical infections (especially weight loss) and clinical disease (diarrhea) make the species of this genus a very significant economic concern. Therefore, this study was conducted in some areas of Wasit Province. A total of 180fecal samples fromgoats, of both sexes and covering different age groups and months, were collected. All fecal samples were examined microscopically, and 75 positive fecal samples were taken for molecular examinationand further analyzed using conventional PCR, sequencing and phylogenetic analysis. Microscopic results showed that the overall infection rate was 41.6%. The incidence of Eimeriaspecies ranged from 5.55% to 22.22% across three different species of the genus Emeria Schneider, 1875, namely E. arloingi(Marotel, 1905), Martin, 1909 (22.22%), E. christenseniLevine, Ivens & Fritz, 1962 (13.88%), andE. hirciChevalier, 1966(5.55%). Regarding the PCR reaction, results from the 18S rRNA, COI gene and genetic sequencing, Confirmed that the fecal samples were positive for EimeriaSchneider, 1875 species.